Ultraviolet Spectrophotometric Method for Determination of Glipizide in Presence of Liposomal/Proliposomal Turbidity - Neelkant Prasad; Roshan Issarani; Badri Prakash Nagori (Journal of Spectroscopy)
A simple and sensitive ultraviolet spectrophotometric method for quantitative estimation of glipizide in presence of lipid turbidity is described to avoid false estimation due to diffraction by turbidity. UV detection was performed at 230 nm, 225 nm, and 235 nm, and the calibration curve was plotted between resultant of absorbance of [230 nm − (225 nm + 235 nm)/2] and concentration of analyte. The calibration curve was linear over the concentration range tested (1–20 μg/mL) with limit of detection of 0.27 μg/mL and limit of quantification of 0.82 μg/mL. Percent relative standard deviations and percent relative mean error, representing precision and accuracy, respectively, for clear as well as turbid solutions, were found to be within acceptable limits, that is, always less than 0.69 and 0.41, respectively, for clear solution and 0.65 and 0.47, respectively, for turbid solution. Conclusively, our method was successfully applied for the determination of glipizide in clear as well as turbid solutions, and it was found that the drug analyte in both types of solutions can be detected from the same calibration curve accurately and precisely and glipizide entrapped in the liposomes or in proliposomal matrix was not detected.